Gross fixed capital formation and productivity in Southeastern Europe - Trpeski, Predrag; Cvetanoska, Marijana (Faculty of Economics & Business, University of Zagreb., 2019)
Capital formation is considered to be an important factor of economic growth both in theoretical and empirical literature. It is generally agreed that the main purpose of economic development is to build capital equipment on a sufficient scale to increase productivity in the economy. Therefore, capital formation makes development possible even with increasing productivity. It is also recognized that gross capital formation has a direct, but also an indirect impact on the productivity. Based on an intensive and a comprehensive literature review, the aim of the paper is to examine the impact of fixed capital investments on productivity in the countries of Southeastern Europe in the period from 2000 to 2017. Albania, Bosnia and Herzegovina, Bulgaria, Croatia, Greece, Macedonia, Montenegro, Romania, Serbia and Slovenia are part of the analysis, except Kosovo which is not a subject of the study due to a lack of data. Beside Southeastern Europen countries, the research is done at the European Union level, and Germany and France are also included as a two leading economies in the European Union. The paper starts from the assumption that fixed capital investments determine the marginal labour productivity, which in turn determines the demand for labour and the employment. In other words, greater investments in fixed capital will increase the marginal labour productivity, which will increase the demand for labour and the employment. In the paper, a regression analysis and correlation are implemented in order to determine and predict the impact of fixed asset investments on productivity. Testing of the series of fixed assets investment and productivity is done by applying the Unit Root test using the Augmented Dickey - Fuller test. Also, a cluster analysis is made and the k-mean clustering method is applied. Results of the study show that changes in productivity are largely explained by changes in gross fixed capital formation at European Union level and in Germany and France, and in these countries there is a higher coefficient of correlation between investments in fixed assets and productivity. A high correlation coefficients are also obtained in Southeastern European countries that are members of European Union, primarily Slovenia, Greece and Romania, while in Croatia this coefficient is slightly lower. An only exception from Southeastern European countries that are members of the European Union is Bulgaria, which has a very low coefficient of correlation between investments in fixed assets and productivity. In nonEuropean Union countries of Southeastern Europe (Macedonia, Serbia, Bosnia and Herzegovina, Montenegro and Albania), changes in productivity cannot be generally explained by the changes in fixed capital investments, and in these countries there is a very low correlation coefficient between gross fixed capital formation and productivity. Using the cluster analysis based on the k-mean clustering method, three clusters are defined: Cluster 1: Croatia and Romania; Cluster 2: Albania, Bosnia and Herzegovina, Bulgaria, Macedonia, Montenegro and Serbia; and Cluster 3: France, Germany, Greece Slovenia and 278 the European Union. Cluster analysis shows that in Cluster 3, which is defined with countries that have high GDP per capita, high employment and low unemployment, the impact of gross fixed capital formation on productivity is greater. On the other hand, in Cluster 2, that includes non-European Union countries (exception is Bulgaria, which is a member of European Union), and is defined with lower GDP per capita, low employment rates and high unemployment, gross fixed capital formation has not a significant impact on productivity.
Keywords: cluster analysis, fixed capital investment, productivity, Southeastern Europe